Identification of Communication Trends in Business Practices Efforts to Increase Productivity and Smooth Communication in the Workplace: Review What Evidences Say - Jamadi; Bulan Prabawani; Widiartanto Widiartanto; Reni Shinta Dewi (Institute of Computer Science (IOCS), 2022)
Successful communication in the workplace is one of the goals of communication in every organization, government, and business. This study identifies the trend that has occurred recently along with the emergence of business communication technology which replaces the conventional method of communication by switching to an exciting way of communication that reaches all employees in every company and organization. To expedite the discussion of this work, we have conducted a series of searches for evidence from published scientific field studies. So that the study evidence data can answer the problems of this study, we conduct an in-depth study involving data coding and evaluation and in-depth interpretation to get an answer that can answer the problem with the principle of validity and convincing. After analyzing the data, we can conclude that many workplace trends have improved communication between employees by utilizing trending technology applications such as digital collaboration applications, unified video conference, mobile device communications, cloud applications, and several other applications that are becoming increasingly popular that keep trending at work today. Thus, it is hoped that these findings will be helpful in the study of communication in other workplace organizations and further studies.